Case Report: Left atrial dissection after mitral valve replacement: intraoperative management under TEE guidance - Wang, Mengyan; Ji, Fucheng; Zhou, Jinfeng (Frontiers in Cardiovascular Medicine, 2024)
Left atrial dissection (LatD) is a very rare complication of cardiac surgery, but it is relatively more common in mitral valve surgery. Transesophageal echocardiography (TEE) plays an important role in timely detection of LatD and accurate assessment of the condition, which are key factors in determining the patient's prognosis. There are two different treatment options for patients with or without circulatory crisis caused by dissection hematoma, namely surgical management and conservative treatment. In this report, we used TEE to quickly detect the cause and severity of LatD, which assisted the surgeon in making appropriate surgical decisions. The patient was successfully surgically treated for LatD.